2000
DOI: 10.2991/jnmp.2000.7.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Lax Pairs, Painlevé Properties and Exact Solutions of the Calogero Korteweg-de Vries Equation and a New (2 + 1)-Dimensional Equation

Abstract: We prove the existence of a Lax pair for the Calogero Korteweg-de Vries (CKdV) equation. Moreover, we modify the T operator in the the Lax pair of the CKdV equation, in the search of a (2 + 1)-dimensional case and thereby propose a new equation in (2+1) dimensions. We named this the (2+1)-dimensional CKdV equation. We show that the CKdV equation as well as the (2+1)-dimensional CKdV equation are integrable in the sense that they possess the Painlevé property. Some exact solutions are also constructed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This equation was introduced by Yu and Toda recently [12] by considering extension of the Calogero KdV equation. [13,14] They further showed that equation (30) was integrable in the sense of Painlevé property.…”
Section: Application To Calogero Kdv Equationmentioning
confidence: 99%
“…This equation was introduced by Yu and Toda recently [12] by considering extension of the Calogero KdV equation. [13,14] They further showed that equation (30) was integrable in the sense of Painlevé property.…”
Section: Application To Calogero Kdv Equationmentioning
confidence: 99%
“…where u is a function in x, y, t variables and subscript stand for partial derivatives w.r.t its variables x, y and t, respectively. The initial form of the mBSchiff equation was given in the form of a partial integrodifferential equation [23][24][25][26][27] where…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper, we focus on investigating the nonlocal symmetry, prolonged system, Bäcklund transformation, CRE solvability, and the exact interaction solutions of the following (2+1)-dimensional modified Bogoyavlenskii-Schiff (mBS) equation [39][40][41][42][43] u…”
Section: Introductionmentioning
confidence: 99%